Convergent validity of 12-item World Health Organization Disability Assessment Schedule (WHODAS 2.0) among people with neck pain - Karklins, Aleksandra; Berzina, Guna; Saltychev, Mikhail (Public Library of Science (PLoS), 2025)
Objective: To explore the convergent validity of 12-item World Health Organization Disability Assessment Schedule (WHODAS 2.0) comparing it to Neck Disability Index (NDI).
Design: Cross-sectional cohort study.
Subjects/patients: 962 patients visiting a university outpatient Physical and Rehabilitation Medicine Clinic due to musculoskeletal complaints.
Methods: Spearman´s rank correlation between WHODAS 2.0 and NDI.
Results: The average age was 49.2 (SD 14.5) years, 67% were women. Of all the possible 143 correlations between WHODAS 2.0 and NDI, 99 (69%) were positive, significant and strong or, at least, moderate. The correlation between the composite scores of two scales was strong. The weakest correlations were seen for the NDI items 'pain intensity and 'headaches'.
Conclusion: Most of the items and the composite scores of the WHODAS and the NDI demonstrated significant positive correlations. Pain intensity, as defined by the NDI, did not correlate with disability severity measured by the WHODAS 2.0. Also, the NDI items 'headaches' and 'sleeping' were associated with the WHODAS 2.0 only loosely. It seems that one of these two scales may not directly be substituted by another. When used simultaneously, The WHODAS and the NDI may complement each other covering comprehensively the different dimensions of functioning among people with neck pain.